Development and approval of live attenuated influenza vaccines based on Russian master donor viruses: Process challenges and success stories. Issue 45 (26th October 2016) - Rudenko, Larisa; Yeolekar, Leena; Kiseleva, Irina; Isakova-Sivak, Irina
Highlights: LAIV has been used in Russia for decades. Russian LAIV consistently provides superior effective protection against influenza. It was incorporated into the WHO global pandemic influenza action plan. A number of Russian LAIVs against pandemic influenza viruses have been prepared. Russian LAIV technology was transferred to a number of developing countries. Abstract: Influenza is a viral infection that affects much of the global population each year. Vaccination remains the most effective tool for preventing the disease. Live attenuated influenza vaccine (LAIV) has been used since the 1950s to protect humans against seasonal influenza. LAIVs developed by the Institute of Experimental Medicine (IEM), Saint Petersburg, Russia, have been successfully used in Russia since 1987. In 2006, the World Health Organization (WHO) announced a Global action plan for influenza vaccines (GAP). WHO, recognizing potential advantages of LAIV over the inactivated influenza vaccine in a pandemic situation, included LAIV in the GAP. BioDiem Ltd., a vaccine development company based in Melbourne, Australia which held the rights for the Russian LAIV, licensed this technology to WHO in 2009. WHO was permitted to grant sub-licenses to vaccine manufacturers in newly industrialized and developing countries to use the Russian LAIV for the development, manufacture, use and sale of pandemic and seasonal LAIVs. To date, WHO has granted sub-licenses to vaccine manufacturers in China (Changchun BCHT Biotechnology Co., Ltd.), India (Serum Institute of India Pvt. Ltd.) and Thailand (Government Pharmaceutical Organization). In parallel, in 2009, IEM signed an agreement with WHO, under which IEM committed to supply pandemic and seasonal candidate vaccine viruses to the sub-licensees. This paper describes the progress made by collaborators from China, India, Russia and Thailand in developing preventive measures, including LAIV against pandemic influenza.